Manajemen Pengendalian Mutu Dalam Produksi Agribisnis pada Kelompok Wanita Tani Ayu Tangkas - Sukanteri, Ni Putu; Suparyana, Pande Komang; Suryana, I Made; Yuniti, Diah; Verawati, Yenny (Journal Galung Tropika, 2020)
Quality control is needed by the company to improve the quality of the products produced so that they are by the company’s standards and by consumer desires. Maintaining the quality of the products made is also necessary to reduce the company’s quality assurance costs. The research objective was to analyze the quality control of the products produced and identify the factors that damage the products produced by the Ayu Tangkas Women Farmers Group (WFG). The method used in this research is the Statistical Process Control (SPC) method with analysis using the p-control chart and the Fishbone Diagram. The population in the study were all products produced by WFG Ayu Tangkas in December 2019. The results showed that the quality of snacks made by WFG Ayu Tangkas, as many as 4280 pieces, were under control. This can be seen from the 28 points between the Lower Control Limit (LCL) and Upper Control Limit (UCL). There are only two points that are above the UCL control limit. The factor that causes deterioration in Ayu Tangkas WFG snacks’ quality is that the ingredients are not measured with certainty using only the snack maker considerations. Besides, they do not use manufacturing machines, so that the sizes are often not the same because there is no definite SOP for the manufacturing process. There is no promotion so that snacks are made still at a constant volume and the use of firewood in the manufacture so that the heat generated is unstable, causing the snacks to burn and break frequently.